Study of mast cells in appendicitis: possible significance - Sharan, Anita; Ingole, N.S. (Tropical Journal of Pathology and Microbiology, 2019)
Background: To study the mean mast cell count per square mm field in different layers of appendix and to correlate the relationship of these with progression of disease and extent of fibrosis. Also to study the possible significance of mast cell counts with different histological changes and relation with clinical presentation. Material and Methods: A total of 120 cases of appendix comprised of 20 cases of normal appendix which served as the control and 100 cases of appendicitis in different phase of evolution of the disease were studied for mast cell counts and its significance was assessed in correlation with the histopathological diagnosis as per the evolution of the disease. Results: Mast cell counts in submucosa were always higher then in mucosa or in muscular propria both in normal and in pathological appendicitis. The increased mast cell count in the mucosal layer was statistically significant in organizing phase than in chronic appendicitis. Submucosal mast cell count did not show any statistically significant difference between different stages of appendicitis and normal appendicitis. The mast cell count in muscularis propria showed statistically significant increase in chronic appendicitis as well as in early acute phase. In appendicitis with grade 2,3 and 4 histology, the total mean mast cell count/sq mm was much higher than in range in grade 1 and grade 5. Conclusion: In acute phase of inflammation there is decrease in the mast cell. In chronic phase of inflammation there is increase in the mast cell counts. A significant increase of mast cells in muscularis propria during early acute phase of appendicitis which was observed in present study has not been described in literature. This finding needs further evaluation to explain the role of mast cells in the development of early acute inflammatory response.